2010
DOI: 10.1002/jsfa.4141
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and qualitative characterisation of globe artichoke head from new seed-propagated cultivars

Abstract: Hybrid artichokes, especially Opal and Madrigal, appear more suitable for the processing industry and also for fresh-cut production due to their highest processing yield and lowest total phenol content. Because of its high total phenol content, Tempo waste represents a possible source of natural antioxidant in the pharmaceutical field and in the food industry (as a food additive).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…scolymus L.), belonging to the Asteraceae (Compositae) family, is an herbaceous perennial plant native to the Mediterranean area (Bianco 2005), where about 90% of world production is found with 1.52 million tons on 133,326 Ha (FAOSTAT 2009, http://faostat.fao.org). Several uses such as (i) human food as a typical component of the Mediterranean diet, (ii) lignocellulosic biomass for energy (Angelini et al 2009;Ierna and Mauromicale 2010;Gominho et al 2011) and paper pulp (Gominho et al 2001(Gominho et al , 2009), (iii) seed oil for biodiesel fuel production , (iv) roots for inulin Melilli 2004, 2010), (v) leaves and heads for pharmaceutical compounds (Fratianni et al 2007;Lattanzio et al 2009;Bonasia et al 2010;Lombardo et al 2010;Pandino et al 2010Pandino et al , 2011, are considered for the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…scolymus L.), belonging to the Asteraceae (Compositae) family, is an herbaceous perennial plant native to the Mediterranean area (Bianco 2005), where about 90% of world production is found with 1.52 million tons on 133,326 Ha (FAOSTAT 2009, http://faostat.fao.org). Several uses such as (i) human food as a typical component of the Mediterranean diet, (ii) lignocellulosic biomass for energy (Angelini et al 2009;Ierna and Mauromicale 2010;Gominho et al 2011) and paper pulp (Gominho et al 2001(Gominho et al , 2009), (iii) seed oil for biodiesel fuel production , (iv) roots for inulin Melilli 2004, 2010), (v) leaves and heads for pharmaceutical compounds (Fratianni et al 2007;Lattanzio et al 2009;Bonasia et al 2010;Lombardo et al 2010;Pandino et al 2010Pandino et al , 2011, are considered for the species.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, little has been up now done in this sector except for some clonal selections carried out to obtain the Romanesco C3 clone from the traditional populations of Castellammare and Terom from Violetto di Toscana (Soressi 2003). Moreover, introduction of new seed-propagated F 1 hybrids such as Madrigal, Concerto, Opal, Tema (Zaniboni 2009;Bonasia et al 2010) and Romolo, as well as the use of Italian micropropagated clones well suited to market demands, represent factors increasing the risk of genetic erosion for autochthonous germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted by Sonnante et al (2008) and Rottenberg and Zohary (1996) data (ii) lignocellulosic biomass for energy and paper pulp, (iii) seed oil for biodiesel fuel production (iv) beverage, (v) nutraceutical purposes . Current research has shown several health benefits, including promotion of blood circulation, induction of choloresis, inhibition of cholesterol biosynthesis and antioxidant effects (Fratianni et al 2007;Lattanzio et al 2009;Lombardo et al 2010;Pandino et al 2010Pandino et al , 2011aBonasia et al 2010).…”
Section: Fig 231mentioning
confidence: 99%
“…Moreover, new seed propagated F 1 hybrids (e.g. Madrigal, Concerto, Opal, and Tema) are now increasingly cultivated (Zaniboni 2009;Bonasia et al 2010). Conversely, the introduction of foreign F 1 hybrids, as well as the use of Italian spring micropropagated clones as a response to market demand, represents a risk of genetic erosion of autochthonous germplasm.…”
Section: Production and Importancementioning
confidence: 99%
See 1 more Smart Citation